2015
DOI: 10.1038/srep10434
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic regulation of the nuclear-coded GCAT and SHMT2 genes confers human age-associated mitochondrial respiration defects

Abstract: Age-associated accumulation of somatic mutations in mitochondrial DNA (mtDNA) has been proposed to be responsible for the age-associated mitochondrial respiration defects found in elderly human subjects. We carried out reprogramming of human fibroblast lines derived from elderly subjects by generating their induced pluripotent stem cells (iPSCs), and examined another possibility, namely that these aging phenotypes are controlled not by mutations but by epigenetic regulation. Here, we show that reprogramming of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 28 publications
4
82
0
3
Order By: Relevance
“…We found that HMEC derived from older women show increased basal traits, altered signal transduction in response to extracellular matrix proteins and evidence of reduced senescence following oncogene expression. We suggest that this is the result of epigenetic changes imposed on HMEC by an agerelated attenuation of the tissue microenvironment (Hashizume et al 2015).…”
Section: Ageing Luminal Cells Exhibit Basal-like Traitsmentioning
confidence: 88%
“…We found that HMEC derived from older women show increased basal traits, altered signal transduction in response to extracellular matrix proteins and evidence of reduced senescence following oncogene expression. We suggest that this is the result of epigenetic changes imposed on HMEC by an agerelated attenuation of the tissue microenvironment (Hashizume et al 2015).…”
Section: Ageing Luminal Cells Exhibit Basal-like Traitsmentioning
confidence: 88%
“…We screened 66 differentially expressed genes associated with CRC progression in 224 colon cancer tissues and 165 adjacent normal tissues from three GEO data sets and found that SHMT2 is important in CRC metabolism. SHMT2, which is responsible for the conversion of serine to glycine, supports cancer cell proliferation in various cancers (5,15,33). SHMT2 is upregulated in CRC and plays an important role in colorectal carcinogenesis (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…By deep learning methods, we found that MET, CPM, SHMT2, GUCA2B, and SCN9A are significantly related to CRC progression. Among these genes, serine hydroxymethyltransferase 2 (SHMT2) plays a regulatory role in the conversion of serine to glycine, which controls cell proliferation (4,5).…”
mentioning
confidence: 99%
“…Rather, the gene was downregulated in old cells. Rejuvenation reversed this repression and restored normal glycine levels in the mitochondria of rejuvenated fibroblasts [37] .…”
Section: Epigenetics and Aging: The Promise Of Rejuvenationmentioning
confidence: 93%